The Lenovo way : managing a diverse global company for optimal performance - Qiao, Gina; Conyers, Yolanda (McGraw Hill-Ascent Audio, 2014)
A powerful book that shows the step-by-step evolution of a new kind of global technology powerhouse, The Lenovo Way is indispensable reading for leaders and managers who deal with strategy, innovation, branding, and HR at any kind of company. It also tells the remarkable story of how two women from very different backgrounds rose to become leaders in Lenovo's journey to the top. The Lenovo Way shows business leaders how to gain market share and develop new business models. The strategies driving Lenovo's ascent to the leading position in the PC industry have been in motion for years, and this book shows how Lenovo, with roots in both East and West, did it. Based on unprecedented access to former and present CEOs and other top managers, The Lenovo Way tells the fascinating story of the rise of this remarkable global brand. It also provides invaluable business lessons for how to use Lenovo's success strategies to advance your own company's success. Building for a decade on its history-making acquisition of IBM's PC business in 2005, today Lenovo is #1 in global PC sales, and it is rapidly gaining in sales of tablets and smartphones. Lenovo is challenging the world's biggest and most powerful brands through innovations and new acquisitions to become an even bigger force in smartphones, servers, and cloud computing, and its CEO has been listed as one of the best in the world. Using the story of Lenovo as a case study illustrating best global practices, The Lenovo Way explains how to: Gain market share by protecting core strengths while seizing new opportunities Create a diverse and effective culture that transcends all borders Lead your company successfully through the chaos of change Make innovation part of your organizational DNA Providing key insights into the topics most critical to leaders of global businesses, the authors explore all the major turning points: from building an iconic brand to streamlining supply chains, while making the transition from a core business of PCs to a new business model. In order to excel in today's marketplace, managers need to create a blueprint for a whole new level of globalization. You must position your company to continue doing what it does best, yet be poised not just to navigate but also to capitalize on change and take advantage of turmoil. Look to the company that has been able to turn a diverse workforce into a global business phenomenon. This is your time to learn how to do it The Lenovo Way.